Investigating genotype-phenotype correlation of limb-girdle muscular dystrophy R8: association of clinical severity, protein biological function and protein oligomerization - Xiongda Liang; Jiameng Si; Hongting Xie; Yuqing Guan; Wanying Lin; Zezhang Lin; Ganwei Zheng; Xiaofeng Wei; Xingbang Xiong; Zhengfei Zhuang; Xuan Shang (Acta Neuropathologica Communications)
Abstract Limb-girdle muscular dystrophy R8 (LGMD R8) is a hereditary muscle disease caused by biallelic defects in E3 ubiquitinated ligase gene (TRIM32). LGMD R8 is featured by high genetic heterogeneity and phenotypic diversity, most pathogenic variants are missense variants located in the NHL domain, but the genotype-phenotype correlation remains unclear. We hypothesized that various missense variants in NHL domain might have different degrees of impact on the structure and function of the protein, thus resulting in disease variability. Firstly, by analyzing present patients’ clinical data, we screen out 4 variants: R394H, D487N, V591M and P619S. Patients homozygous for the aforementioned variants exhibited significant phenotypic variability, including variations in age of onset and age of any walking aid (AWA). Then, bioinformatics analysis, cellular functional experiment and biophysical assay were used to measure the effect of above variants in TRIM32 protein oligomerization and ubiquitination to target substrates. And they revealed distinct differences in the intrinsic E3 ligase activity among various mutant TRIM32 proteins, which corresponded to differences in their oligomerization status. In conclusion, our results showed a correlation between clinical severity, protein function and oligomerization state in patients homozygous for missense variants in NHL domain. It is the first time to reveal a connection between TRIM32 variant with LGMD R8 phenotype and this finding provided valuable reference in predicting disease severity and more precise guidance to affected family on genetic counseling.